Waste Corn-Cob Cellulose Supported Copper Catalyst for Click and Aza-Michael Reactions - Sarkar, Shaheen M.; Sultana, Tahnim; Biswas, Tapan Kumar; Lutfor, M. R.; M. M., Yusoff (Royal Society of Chemistry, 2016)
We prepared a highly active cellulose supported poly(amidoxime) Cu-catalyst 2 by the surface modification of waste corn-cob cellulose through graft copolymerization process (Scheme 1). The Cu-catalyst 2 was efficiently promoted the click reaction1 of organic azides and terminal alkynes including the three-component cyclization of a variety of alkynes, organic halides, and sodium azide (Scheme 2). The catalyst with 50 mol ppm (0.00050 mol%) to 0.05 mol% Cu promoted the cycloaddition with a TON of up to >18800, and was reused four times without loss of catalytic activity. Moreover the catalyst was also promoted the Aza-Michael reaction of aliphatic amines with a variety of olefins to give the corresponding products in up to 97% yield.